ANALISIS TINGKAT PEMAHAMAN PEMILIK KOS TENTANG PAJAK KOS DI KECAMATAN TAMPAN - Rika, Rika; Gusnardi, Gusnardi; Riadi, RM. (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aimed to determine how much the level of understanding about boarding owners and boarding taxes in the Tampan District. The research was conducted in Pekanbaru. This type of research is a descriptive quantitative study with a sample of 55 boarding owners who have a number of boarding rooms more than 10 (ten) rooms. Data obtained from questionnaires are then analyzed by categorizing the average results of the questionnaire in four categories: very low, low, high, and very high. The results showed the average results of the questionnaire on the Rule indicators on the imposition of boarding fees was 0.4 (low), the indicator of boarding tax objects was 0.43 (low), the basic indicators of imposition and boarding tax rates were 1.2 (low), the cost of collecting tax indicators is 0.9 (low), the Local tax return filling indicator is 0.8 (low), the cost of tax payment is 1.34 (low), and the tax charge indicator is 1.07 (low) ). So the overall results of the study indicate that the understanding of boarding owners in classified good.Key Words: Understanding, Boarding Taxes, Boarding Owners